2020
DOI: 10.1088/1755-1315/553/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

A study to expose quail eggs for two different periods of incubation with low-intensity magnetic flooding on the growth of chicks and their productive performance

Abstract: An experiment was conducted in the fields of the poultry unit - Livestock Division - Nineveh Research Department, to find out the effect of using low-intensity magnetic flux (110 Gaos) in two periods of incubate quail eggs, on the growth and production performance of the resulting birds, the results showed a significant increase (P ≤0.05) for the magnetic flux treatment on control treatment for hatchability% and fertility%, the percentage of dead embryos decreased significantly (P ≤0.05) for the second exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In addition El-Sabry et al (2018), [24]found that hens' eggs exposed to magnetic flux showed absolutely the simplest values of hatching indices. In the same context, Ibrahim et al [18]observed improvements in hatchability and BW at 1 and 4 weeks of age in response to exposure quail eggs to 110 Gauss MF during the either first or second week of the incubation period. Recently,Younis and Qasim [17] reported substantial increase in hatchability and live BW until 42 days of age when Ross 308 broiler breeders' eggs were exposed to 1800 Gauss MF for 30, 60, and 90 min.…”
Section: Hatchability and Bw At Hatchmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition El-Sabry et al (2018), [24]found that hens' eggs exposed to magnetic flux showed absolutely the simplest values of hatching indices. In the same context, Ibrahim et al [18]observed improvements in hatchability and BW at 1 and 4 weeks of age in response to exposure quail eggs to 110 Gauss MF during the either first or second week of the incubation period. Recently,Younis and Qasim [17] reported substantial increase in hatchability and live BW until 42 days of age when Ross 308 broiler breeders' eggs were exposed to 1800 Gauss MF for 30, 60, and 90 min.…”
Section: Hatchability and Bw At Hatchmentioning
confidence: 91%
“…They expect that technique will be the future ones for these purposes. In the same context, Ibrahim et al [18] reported that using low-intensity magnetic flux (110 Gauss) increased hatchability, body weight (BW) at 1 and 4weeks of age, and feed conversion ratio in quails. Moreover, the hatchability of broiler-breeders' eggs was (19).…”
Section: Introductionmentioning
confidence: 98%
“…[15,27] The results are in agreement with Khudiar and Ali [28] who reported a significant increase in egg production and reduced mortality rate in commercial egg-layers flocks exposed to MF. Ibrahim et al [13] also showed a significant increase in hatching percentage, embryos surviving, sexual maturity and food conversion ratio (kg feed/kg egg) of quail eggs exposed to lowintensity magnetic flux (110 Gaus). Keirs et al [29] reported also an increase in hatchability of eggs subjected to MF of 0.07 T (700 Gauss) during storage for 20-40 min.…”
Section: Laying Performancementioning
confidence: 94%
“…[9] The application of magnetic technology is an innovative method that can be used to improve the overall productivity and physiological health of aged quails. Hence, there have been numerous studies demonstrated the benefits of exposure to MF on productive performance, hematological, biochemical, and hormonal parameters of aged inactive laying quails, [10] productive, [11][12][13] and reproductive [14] aspects of birds, increases blood flow, improves the immune system, [11] appositive effects on the endocrine and neurological system, reproductive performance, and physiology, [14] as well as to stimulate blood and lymphatic flow, hormone secretion, and the delivery of nutrients to all body cells. [15] The other possibility that can assist in enhancing the productivity and immunity capabilities of poultry is magnetizing the drinking water and a alliterating the physics of water by exposure to MF.…”
Section: Introductionmentioning
confidence: 99%